COVID-19 Vaccination Does Not Affect Reproductive Health Parameters in Men - Reschini, Marco; Pagliardini, Luca; Boeri, Luca; Piazzini, Francesca; Bandini, Veronica; Fornelli, Gianfranco; Dolci, Carolina; Cermisoni, Greta Chiara; Viganò, Paola; Somigliana, Edgardo; Coccia, Maria Elisabetta; Papaleo, Enrico (Frontiers in Public Health, 2022)
With the implementation of COVID-19 vaccine up-take, doubts regarding the impact of immunization on future fertility have begun to emerge. We have examined vaccine safety on male reproductive health. We set up a multicentre (three infertility centres), retrospective study in order to assess semen parameters and fertilization rate of one hundred-six men in a pairwise comparison between the first and second assisted reproduction technology (ART) attempt, performed respectively before and after COVID-19 vaccination. Median time (range) between the first vaccine dose and the second ART cycle was 75 days (39-112). Semen parameters did not change before and after the exposure. Fertilization rate was also similar before and after vaccination. Twenty-five patients (24%) were oligozoospermic before the vaccination while 26 (25%) after the exposure (P=0.87). Severe asthenozoospermia were present in 11 patients before as well as after the exposure. No difference was observed even after considering different types of vaccines (mRNA or viral vector). COVID-19 vaccination did not affect sperm quality and fertilization capacity of men undergoing ART treatments and should be considered safe for men’s reproductive health.